Public Policy and the Response to Covid-19 - Hristina Runcheva Tasev; Aneta Stojanovska-Stefanova (Udruženje za političke nauke Srbije, Univerzitet u Beogradu – Fakultet političkih nauka, 2021)
The paper analyses the latest developments of the impact of scientific and technical expertise in public policy-making on how to deal with the effects of the pandemic. The authors explore the reasons why the same public policies give quite different results in dealing with the dynamics of the pandemic in different countries and regions. Following the William N. Dunn’s model of public policy analysis, the global response to the pandemic shows that there is an urgent need for new policy decisions and reconsideration of the effects of non-decisions. We also explore how the policy responses for change and adaptation to the pandemic have been formulated and delivered to the public and how the narratives and emotions can influence public behaviour in times of crisis. We conclude by stressing the fact that public policies are not static and should be reformulated on the basis of changing circumstances, needs and experience created by crisis.
Keywords: Pandemic, Covid-19, Public Policy, Policy Analysis